Chance factors in football: goals, conversions, Schedule and season - Lames, M. (13th World Congress of Performance Analysis of Sport and 13th International Symposium on Computer Science in Sport. IACSS&ISPAS 2022, 2023)
Modelling game sports like football as dynamic interaction processes with emergent behavior supports the notion of chance factors as regular part of the structure of performances. In addition to these within-match chance factors, on the larger scale of a football season chance phenomena are relevant as well. This paper identifies four chance factors: goal scoring, conversion of scoring opportunities, match scheduling over a season, and number of points per season needed to achieve success. Empirical examples from German Bundesliga and English Premier League are given.